New South Wales: Australia area 310,700 Sqr miles population 830,000. Sydney the metropolis of the colony population 250,000 (Thomas Richards, 1884)
[Opis linii kolejowej i miasta New South Wales ark. 1].
by authority: Thomas Richards.
Keywords: Kolejnictwo; mapy kolejowe; Australia; Kartografia; Lithgow (Australia); w kartografii; Nowa Południowa Walia (Australia); Zig Zag (1860 ca-)